Karakteristik Zat Warna Antosianin (Adenanthera pavonina L) dari Kulit Biji Saga sebagai Pewarna Alami Menggunakan Metode Soxhletasi - Halimatuddahliana; Pandia, Setiaty; Hasmita, Fira Ayu (Jurnal Teknik Kimia USU, 2020)
In general, dyes that are used in daily life using synthetic dyes. One material that can be used for natural pigment are from saga seeds (Adenanthera pavonina L). Saga (Adenanthera pavonina L) is a tree that has small red seeds which is one source of anthocyanin which can be used as natural dyes, antioxidants and anticarcinogens. In this research aims to find the type of solvent and the best extraction time used for the extraction of anthocyanin from saga seeds. Extraction of anthocyaninÂ  from saga seeds used soxhletation method. The variables this research there are the type of solvent (5% citric acid 5% and citric acid 5% (w/v)) and the extraction time (30, 60, 120 minutes). The parameters used are qualitative and quantitative analysis (total yield, total anthocyanin concentration, antioxidant activity, intensity colour and lethal concentration of anthocyanin toxicity in extracts). The result observationaling show that the extraction from saga seeds that have best characteristics in aquadest-citric acid 5% solvent extract yield with extraction time 120 minutes 64.448% (w/w), total anthocyanin with extractions time 120 minutes 100.026 (mg/L), color intensity with extraction time 60 minutes 0.528, antioxidant activity (IC50) 11.622 ppm and toxicity activity with extraction time 60 minutes 63.326 ppm.